COLLETOTRICHUM PIPER LONGUM LEAF BLIGHT SURVEY ON IN VIDARBHA REGION OF MAHARASHTRA (Journal of Plant Disease Sciences, 2023)
The Colletotrichum blight of Piper longum caused by Colletotrichum gloeosporioides. The infection of blight was start since the month of July and it increasesasthe moisture in the atmosphere increases. The data collected fromroving survey of Colletotrichum leaf blight of Piper longum during June to December, 2021 showed average incidence and intensity of disease in Akot tehsil 22.04 and 15.84 per cent respectively and in Anjangaon tehsil 22.56 per cent incidence with 16.29 per cent disease intensity, respectively. The disease found more severe in second year plantation with incidence 22.90 per cent with intensity 20.81 per centas compared to first year plantation with disease incidence 17.17 per cent with disease intensity11.62 per cent, respectively.
Keywords: Piper longum; Colletotrichum leaf; blight; Colletotrichum; gloeosporioides; Survey